Adult Burn Inpatients Have Increased Burn Severity and Mortality Compared to Children in a Retrospective Analysis of the 2017 National Inpatient Sample 2017 - Amar Desai; Noelle Desir; Shari Lipner (Mattioli1885, 2023)
Introduction: Socioeconomic status and comorbidities are associated with increased mortality in external surface burn patients of all ages, however differences in the impact of demographics between pediatric and adult burn populations has not been adequately studied. Objective: The purpose of this article is to explore the presentation, management, and outcomes of external surface burns between different age groups. Methods: The 2017 National Inpatient Sample (NIS) was queried for patients with any diagnosis of external body surface burns. Demographics, comorbidities, complications, total charges, length of stay (LOS), number of procedures undergone (NPU), and time from admission to first procedure (TFP) were identified. Univariate and multivariable analyses were used to identify statistical associations with age. Results: 52,335 inpatients were identified with burns, with the majority male (63.6%) and adults (81.8%). Mean age was 50.5 (SE: 0.1) and 5.5 (SE: 0.1) years for adults and children, respectively. Adults had higher incidence of hypertensive disease (43.5% vs. 1.4%), diabetes mellitus (24.1% vs. 0.3%), and obesity (11.7% vs. 1.6%) than children (p<0.001). Adults vs. children had higher odds for mortality (OR 4.26, 95% CI 3.08-5.89), sepsis (OR 5.16, 95% CI 4.10-6.48), and pneumonia (OR 4.26, 95% CI 3.30-5.50). Conclusion: In a national cohort of inpatients with external surface burns, total charges, LOS, NPU, TFP, and odds for complications varied by age. Pediatric patients more often had lower household incomes; however, adults had significantly higher odds for mortality suggesting that age and comorbidity status are more impactful on burn outcomes than socioeconomic status.